Surface plasmon satellites in core-level X-ray photoemission spectra of late transition-metal compounds - Srivastava, Sanjay Kumar (Array, 2008)
Summary: The origin of satellites in 2p core level of late transition metal compounds are studied using plasmon theory. The calculated values of energy separation and relative intensity agree well with the experimental values and the theoretical calculations by Kozo Okada et al. The excitation of surface plasmons in 2p core level X-ray photoemission spectra of transition metal dihalides is discussed